2013
DOI: 10.1123/pes.25.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Bizzy Break! The Effect of a Classroom-Based Activity Break on In-School Physical Activity Levels of Primary School Children

Abstract: The school has been identified as a key setting to promote physical activity. The purpose of this study was to evaluate the effect of a classroom-based activity break on in-school step counts of primary school children. Data for 90 children (49 boys, 41 girls, 9.3 ± 1.4 years) from three Irish primary schools is presented. In each school one class was randomly assigned as the intervention group and another as controls. Children’s step counts were measured for five consecutive days during school hours at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 24 publications
1
62
1
4
Order By: Relevance
“…This is an interesting finding since females are often shown to be less active than males, especially during school (Murtagh et al, 2013). It can be suggested that the physical activity accumulated by both males and females during the lessons are similar because all children present in the classroom were presented with the same opportunities to participate and engage in the same activities during the lessons and were requested to do so as part of their teacher's instruction of the English and Mathematics lessons.…”
Section: Children's Physical Activity Levelsmentioning
confidence: 95%
See 2 more Smart Citations
“…This is an interesting finding since females are often shown to be less active than males, especially during school (Murtagh et al, 2013). It can be suggested that the physical activity accumulated by both males and females during the lessons are similar because all children present in the classroom were presented with the same opportunities to participate and engage in the same activities during the lessons and were requested to do so as part of their teacher's instruction of the English and Mathematics lessons.…”
Section: Children's Physical Activity Levelsmentioning
confidence: 95%
“…A study which evaluated Irish primary school children's physical activity levels during the segmented school-day found that the children accumulated a mean of 18.6 min of MVPA (Murtagh et al, 2013) during the whole school day. Murtagh et al (2013) reported that children achieved the least amount of physical activity during class time with the accumulation of only 8 min of MVPA. This is much lower than the present study which accrued a mean of 15 min of MVPA during the same period of the day.…”
Section: Children's Physical Activity Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants will be asked to wear the accelerometers during normal school day activities [18,48] except while swimming, for five consecutive school days of baseline and intervention measurement. The age and sex of the children in each class will be recorded and an identifying code paired with an accelerometer will be assigned to each student.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…However, many children are not meeting the recommended guidelines of 60 min of daily moderate‐to‐vigorous PA . The school has been identified as an ideal setting in which to promote PA as it gives access to children regardless of age, ethnicity, gender and socio‐economic class . Potentially beneficial initiatives range from school‐wide PA and nutrition interventions to stand‐alone programmes such as ‘walking buses’ and playground redesign .…”
mentioning
confidence: 99%